The Effect of Using Audiovisual Media on Students' Mathematics Learning Outcomes in Online Learning Supplements - Sazali, Nur Safira; Arjudin, Arjudin; Kurniawan, Eka (Balai Publikasi Indonesia, 2024)
This research aims to determine the effect of using audiovisual media on students' mathematics learning outcomes in online learning supplements. This type of research is experimental research. The population in this study were class VIII students, with the sample determined using random sampling techniques. The sample in this study consisted of 76 students, namely class VIII-A as the experimental class and class VIII-B students as the control class. The instrument used is a test of student learning outcomes. The data analysis used is the normality test and homogeneity test as a prerequisite test and the t test as a hypothesis test and effect size test to determine whether there is an influence from the use of audio-visual media on student learning outcomes. Based on the results of hypothesis testing using the t test, the significance level was obtained obtained And where these results show that so that rejected and accepted. The effect size test results obtained a result of 0.804 which is in the high category, which means that there is an influence of the use of audio-visual media on students' mathematics learning outcomes in online learning supplements